STRATEGI PEMANFAATAN APLIKASI TIK TOK SEBAGAI MEDIA DAKWAH DI ERA MILENIAL: ANNISA PUTRI - Putri, Annisa (Qawwam : The Leader's Writing, 2024)
The use of the Tiktok application in the process of delivering da'wah has had a positive response. So the statement that Tiktok started as an application that only contained useless video content has now turned into an application that contains spiritual and Islamic educational content which has a positive impact and response for its users, one of which is da'wah to compete with content that is deviant or not. useful for Muslims as a method of delivering da'wah that is relevant in the current technological era. For this research, the author used qualitative research methods, where this qualitative research is descriptive and tends to use analysis. Process and meaning are more emphasized in qualitative research. The next method that the author uses in writing this article is a literature review, which has two stages in writing, the first is the selection stage or choosing articles, the second is the stage of analyzing the content of the article in detail. Based on the research above, the author concludes that in preaching it is necessary to keep up with the times so that the process of inviting, calling and educating or conveying goodness by including elements of da'wah in it can be well received, especially using an application that is already widely used in various circles, namely TikTok. Da'wah content can also compete with other content spread on Tiktok by fulfilling the existing requirements on Tiktok with likes, comments, copy links and so on as support for the account so that the account remains FYP or continues to appear on other people's homepages, so that more and more The more people who see it, the more they will be invited and educated by the content